The prevalence and determinants of active tuberculosis among diabetes patients attending a primary health care clinic in Cape Town, South Africa - O'Jiaku-Okorie, Adaeze (Institute of Infectious Disease and Molecular Medicine, 2016)
Background: The number of studies addressing the association between diabetes mellitus (DM) and tuberculosis (TB) in the context of sub - Saharan Africa (SSA) is limited and fewer studies have determined whether DM is associated with TB among patients attending DM c linics. We aimed to assess the prevalence of TB among a population, diagnosed and receiving treatment for DM at a primary care clinic, and to identify significant risk factors of prevalent TB cases. Methods In this cross - sectional study, adult DM patients attending an outpatient clinic at a South African township were evaluated for TB using Xpert MTB/RIF testing (Xpert) and other conventional methods - clinical symptom screening, smear microscopy, chest x - ray, and culture. Socio - demographic and biochemical information were collected using the Who's STEPwise approach to surveillance of chronic disease risk factors. Findings 451 DM patients were screened for TB. 16 DM patients were diagnosed with TB, following screening giving a prevalence rate of 3 · 55% or 35 · 48 per 1000 people [95% CI: 2 · 18 - 5 · 72]. 37 · 50% (n=6) of TB cases reported at least one clinical symptom of TB [95% CI: 17 · 34 - 63 · 11%]. 62 · 5% (n=10; 95% CI :) of TB cases were HIV - positive. In a multivariate analysis, HIV (OR : 14 · 58 , p<0 · 001) and haemoptysis (OR 24 · 48, p<0 · 001) were strongly associated with prevalent TB. Identified associations were not modified by age or gender. There were no significant differences in either fasting plasma glucose or HbA1c levels between TB and non - TB DM participants. Discussion Prevalence of TB among DM population was higher than in the general population based on national estimates, highlighting an important DM - TB association in an SSA setting. HIV as a significant risk factor for TB confirms its position as a major driver in TB epidemic overall and in T2DM patients. Two - thirds of prevalent TB cases reported no TB symptoms, suggesting further research is needed to identify more accurate TB screening strategies for DM patients, particularly in HIV - infected persons, to facilitate early detection and treatment of prevalent TB in this population group.